2002
DOI: 10.1136/bmj.325.7367.752
|View full text |Cite
|
Sign up to set email alerts
|

Home based exercise programme for knee pain and knee osteoarthritis: randomised controlled trial

Abstract: Objectives To determine whether a home based exercise programme can improve outcomes in patients with knee pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
287
2
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(309 citation statements)
references
References 21 publications
13
287
2
7
Order By: Relevance
“…Some evidence suggests that lack of physical activity leads to muscle strength destabilization of the knee, with a greater risk of developing or worsening OA (8). Accordingly, aerobic exercise (9) and resistance exercise (10,11) have been shown to be beneficial for OA patients and have resulted in improved gait and function. Moderate levels of physical activity are recommended for persons with OA, provided the activity is not painful (12).…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence suggests that lack of physical activity leads to muscle strength destabilization of the knee, with a greater risk of developing or worsening OA (8). Accordingly, aerobic exercise (9) and resistance exercise (10,11) have been shown to be beneficial for OA patients and have resulted in improved gait and function. Moderate levels of physical activity are recommended for persons with OA, provided the activity is not painful (12).…”
Section: Introductionmentioning
confidence: 99%
“…Compliance to treatment is important in attaining treatment goals. When a physical exercise regimen is prescribed, adherence to this regimen is crucial in preserving physical performance and function (in terms of observed walking distance and self-reported disability, respectively) and in reducing pain for patients with knee OA (5).…”
Section: Introductionmentioning
confidence: 99%
“…85 Ettinger (1997) 86 van Baar (1998) 87 Maurer (1999) 88 O'Reilly (1999) 89 Péloquin (1999) 90 Deyle (2000) 91 Hopman-Rock (2000) 92 Baker (2001) 93 Fransen (2001) 94 Halbert (2001) 95 Patrick (2001) 96 Belza (2002) 97 Thomas (2002) 98 Topp (2002) 99 Foley (2003) 100 Quilty (2003) 101 Talbot (2003) 102 Hughes (2004) 103 Keefe (2004) 104 Lin (2004) 105 Messier (2004) 106 Ravaud (2004) 107 Bennell (2005) 108 Cochrane (2005) 109 Tak (2005) 110 Hay (2006) 34 Mikesky (2006) 111 Fransen (2007) 112 Hinman (2007) 113 Wang (2007) 114 Subtotal (I 2 = 0.0%; p = 0.990) Sensitivity analyses were performed for advice and information, and exercise intervention studies, with results showing minimal differences in the pooled effect estimates after exclusion of studies with a high risk of bias.…”
Section: Clinical Effectiveness Of Primary Care Interventions For Ostmentioning
confidence: 99%
“…The Acupuncture, Physiotherapy and Exercise (APEX) trial, 202 which incorporated a more intensive exercise intervention that was supervised and progressed over six treatment sessions, resulted in greater improvements in pain than the exercise programme in the TOPIK trial. 34,203 Similarly, other recent trials 30,98 and reviews 204 showed small to moderate, short-term reductions in knee pain and disability that are not sustained in the long term. 192 Exercise is clearly worth doing but we need to find out if, and how, the beneficial effects can be maintained over time.…”
Section: Introductionmentioning
confidence: 99%